Experimental study on similar materials in model test based on orthogonal design. Issue 4 (March 2021) - Li, Jianguang; Zou, Huisong; Sun, Gengyu; Zhou, Ziyi; Zeng, Lingqi
Abstract: The selection of simulation materials of aquiclude has an important influence on the results of the model test, and has a high requirement in terms of mechanics and hydrologic properties. According to the high quality of river sand as aggregate, cement and gypsum mixed aqueous solution as cementing material, organic silicon mixture similar material as additive, in accordance with the principle of orthogonal test design, sand-binder ratio, cement plaster - and concentration of organic silicon as factors, each factor is equipped with four levels, specimen preparation into under the different ratio of similar model, carries on the uniaxial compressive strength test, splitting test, penetration test and the moisture content test under the different ratio of compressive strength, tensile strength, permeability coefficient and softening coefficient, By means of the range analysis method of orthogonal experiment, the influence degree of each factor level on the similar material is summarized, and it is concluded that the ratio of sand gum to mechanical properties has great influence, and the concentration of organosilicone water has obvious influence on the water rational energy.The new solid-flow coupling simulation material developed in this paper can provide a new scheme for the model test of water-involved problems such as mining under confined water, water-retaining mining and construction in water-rich area, and has high application value.